INJAUAN FAKTOR INTERNAL DAN EKSTERNAL PENYEBAB KESULITAN BELAJAR SISWA PADA MATA PELAJARAN BIOLOGI DI SMA NEGERI 1 PADANG GELUGUR KABUPATEN PASAMAN - Irawati, Irawati; Nurhadi, Nurhadi; Risdawati, Renny (Pendidikan Biologi, 2013)
ABSTRACTLearning difficulties from the students is influenced by several factors, such as internal and external factors of the school. The aims of this research to know the factors that cause learning difficulties of the students in the biology subjects. This research is a descriptive research. The population in this research was students of class X, XI IPA, IPA XII SeniorÂ  high school 1 Padang gelugur Pasaman who registered in 2012/2013 academic year that amounted of 475 students. The members of the population that used as sample were 25 % of the 475 students, who amounts 120 students, and implemented in February 2013. From the result of the research, the percentage of data obtained from internal factors on intelligence indicators of students in learning, the students attitudes in learning, the talent of students to develop their hobby in learning, the students interest give priority to their desire in learning, the students motivation in learning, with a value of 54.52 % with criteria quite influential. While the percentage of external factors that influence the students in learning difficulties on biology subjects with indicators of how the parents educate the children , the relationship between the family , the situation of house , economy of the family , the teachers teaching methods , curriculum , library , the condition of school buildings , school discipline , playmate , mass media with a value of 52.12 % with criteria quite influential. From the research it can be concluded that the internal and external factors enough to affect learning difficulties of the students.Â